Surgical vs nonoperative treatment for lumbar disk herniation: the Spine Patient Outcomes Research Trial (SPORT) observational cohort - Weinstein, James; Lurie, Jon D.; Tosteson, Tor D.; Skinner, Jonathan S.; Hanscom, Brett; Tosteson, Anna N.A.; Herkowitz, Harry; Fischgrund, Jeffrey; Cammisa, Frank P.; Albert, Todd; Deyo, Richard A. (JAMA, 2006)
Context For patients with lumbar disk herniation, the Spine Patient Outcomes Research Trial (SPORT) randomized trial intent-to-treat analysis showed small but not statistically significant differences in favor of diskectomy compared with usual care. However, the large numbers of patients who crossed over between assigned groups precluded any conclusions about the comparative effectiveness of operative therapy vs usual care.